GRAVIDEZ PRECOCE NA CONCEPÇÃO DOS ADOLESCENTES - Márcia Figueira Canavez; Enedina Soares; Naiara Kícila Santos Maia Silva; Patrícia Martins Chaves (Revista de Pesquisa Cuidado é Fundamental Online)
MárciaFigueiracanavez                                                                          EnedinaSoares                                                                   Naiara Kícila dos Santos Maia Silva                  Patrícia Martins Chaves